2021
DOI: 10.21037/tau-21-111
|View full text |Cite
|
Sign up to set email alerts
|

Pazopanib in patients with metastatic renal cell carcinoma: a single-center, real-world, retrospective Chinese study

Abstract: Background: The efficacy and safety of pazopanib in patients diagnosed with metastatic renal cell carcinoma (mRCC) have been demonstrated by a Chinese subgroup analysis of the COMPARZ (Pazopanib Versus Sunitinib in the Treatment of Locally Advanced and/or Metastatic Renal Cell Carcinoma) trial.However, the real-world data are still unknown. This single-center, retrospective study was designed to verify the real-world effects of pazopanib in Chinese patients with mRCC. Methods: Patients with mRCC and a clinical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Indeed, the CheckMate-214 study also suggested that intermediate-risk patients be further stratified to more accurately predict treatment outcomes (13). Several previous studies have reported survival differences between patients with IMDC 1 vs. 2 risk factors (16)(17)(18)(19). However, previous first-line randomized controlled studies used sunitinib as the standard treatment option, and data on the treatment of IMDC favorable-and intermediate-risk patients with pazopanib are lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the CheckMate-214 study also suggested that intermediate-risk patients be further stratified to more accurately predict treatment outcomes (13). Several previous studies have reported survival differences between patients with IMDC 1 vs. 2 risk factors (16)(17)(18)(19). However, previous first-line randomized controlled studies used sunitinib as the standard treatment option, and data on the treatment of IMDC favorable-and intermediate-risk patients with pazopanib are lacking.…”
Section: Introductionmentioning
confidence: 99%